2008
DOI: 10.1111/j.1365-294x.2008.03927.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal population structure of the chestnut blight fungus in expanding ranges in southeastern Europe

Abstract: Expanding populations are often less genetically diverse at their margins than at the centre of a species' range. Established, older populations of the chestnut blight fungus, Cryphonectria parasitica, are more variable for vegetative compatibility (vc) types than in expanding populations in southeastern Europe where C. parasitica has colonized relatively recently. To test whether vc types represent clones, we genotyped 373 isolates of C. parasitica from southern Italy, Romania, Bulgaria, Macedonia, Greece and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
186
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(212 citation statements)
references
References 66 publications
(115 reference statements)
15
186
4
1
Order By: Relevance
“…In both continents, the genetic diversity of C. parasitica populations seemed lower than in Japan and China, the native area of C. parasitica (for example Liu and Milgroom, 2007). Although the recent analysis of South-Eastern European populations showed a clonal expansion of C. parasitica likely from Italy (Milgroom et al, 2008), genetic analyses of populations from the Atlantic part of Europe suggested that other populations genetically divergent from Italian populations could have been introduced and would spread clonally (Breuillin et al, 2006;Braganca et al, 2007;Montenegro et al, 2008;Robin et al, 2009). However, in contrast to Eastern European populations in which only one mating was generally detected (Milgroom et al, 2008), in these Western populations both mating types were often found allowing sexual reproduction among isolates in this heterothallic haploid species (Braganca et al, 2007;Dutech et al, 2008;Robin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both continents, the genetic diversity of C. parasitica populations seemed lower than in Japan and China, the native area of C. parasitica (for example Liu and Milgroom, 2007). Although the recent analysis of South-Eastern European populations showed a clonal expansion of C. parasitica likely from Italy (Milgroom et al, 2008), genetic analyses of populations from the Atlantic part of Europe suggested that other populations genetically divergent from Italian populations could have been introduced and would spread clonally (Breuillin et al, 2006;Braganca et al, 2007;Montenegro et al, 2008;Robin et al, 2009). However, in contrast to Eastern European populations in which only one mating was generally detected (Milgroom et al, 2008), in these Western populations both mating types were often found allowing sexual reproduction among isolates in this heterothallic haploid species (Braganca et al, 2007;Dutech et al, 2008;Robin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although the recent analysis of South-Eastern European populations showed a clonal expansion of C. parasitica likely from Italy (Milgroom et al, 2008), genetic analyses of populations from the Atlantic part of Europe suggested that other populations genetically divergent from Italian populations could have been introduced and would spread clonally (Breuillin et al, 2006;Braganca et al, 2007;Montenegro et al, 2008;Robin et al, 2009). However, in contrast to Eastern European populations in which only one mating was generally detected (Milgroom et al, 2008), in these Western populations both mating types were often found allowing sexual reproduction among isolates in this heterothallic haploid species (Braganca et al, 2007;Dutech et al, 2008;Robin et al, 2009). The studies in the Atlantic part of Europe were performed with phenotypic markers for which the genetic determinants have not been completely elucidated (that is vegetative compatible (vc) types; Robin et al, 2000;Braganca et al, 2007;Montenegro et al, 2008;Robin et al, 2009) or with molecular markers, but for a low number of sampled populations (Breuillin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because continuous admixture between disparately distributed populations can be detected from discordant genealogies for multiple genetic loci and/or low levels of population differentiation and high numbers of migrants (Geiser et al 1998;Fisher et al 2002;Zhou et al 2007;Milgroom et al 2008). Conversely, concordance among genealogies for multiple loci and diminished gene flow due to ecological, geographical or historical processes are generally regarded as useful indicators of species divergence (Avise and Wollenberg 1997;Barraclough and Nee 2001).…”
Section: Introductionmentioning
confidence: 99%
“…d Nei's genetic diversity (Nei 1973) Table 1 Microsatellite analysis to determine the genotypic and genetic diversities, and the occurrence of multilocus haplotypes (MLH) among three sub-populations, the GAMULT group of isolates and the entire sampled population of Cylindrocladium parasiticum isolated from peanuts in Georgia other haplotypes that were also collected, or by simple recombinations with similar haplotypes. The simple loops likewise suggest convergent mutations or recombinations (Milgroom et al 2008;Posada and Crandall 2001). The only exception to this pattern is MLH no.…”
Section: Discussionmentioning
confidence: 99%